Isothiocyanates: cholinesterase inhibiting, antioxidant, and anti-inflammatory activity - Franko Burčul; Ivana Generalić Mekinić; Mila Radan; Patrick Rollin; Ivica Blažević (Taylor & Francis Group, 2018)
Finding a new type of cholinesterase inhibitor that would overcome the brain availability and pharmacokinetic parameters or hepatotoxic liability has been a focus of investigations dealing with the treatment of Alzheimer's disease. Isothiocyanates have not been previously investigated as potential cholinesterase inhibitors. These compounds can be naturally produced from their glucosinolate precursors, secondary metabolites widely distributed in our daily Brassica vegetables. Among 11 tested compounds, phenyl isothiocyanate and its derivatives showed the most promising inhibitory activity. 2-Methoxyphenyl ITC showed best inhibition on acetylcholinesterase with IC50 of 0.57 mM, while 3-methoxyphenyl ITC showed the best inhibition on butyrylcholinesterase having 49.2% at 1.14 mM. Assessment of the antioxidant efficacy using different methods led to a similar conclusion. The anti-inflammatory activity was also tested using human COX-2 enzyme, ranking phenyl isothiocyanate, and 3-methoxyphenyl isothiocyanate as most active, with ∼99% inhibition at 50 μM.